Eukaryotic Translation Initiation Factor 4E Availability Controls the Switch between Cap-Dependent and Internal Ribosomal Entry Site-Mediated Translation - Svitkin, Yuri V. (American Society for Microbiology, 2005)
Translation of m(7)G-capped cellular mRNAs is initiated by recruitment of ribosomes to the 5′ end of mRNAs via eukaryotic translation initiation factor 4F (eIF4F), a heterotrimeric complex comprised of a cap-binding subunit (eIF4E) and an RNA helicase (eIF4A) bridged by a scaffolding molecule (eIF4G). Internal translation initiation bypasses the requirement for the cap and eIF4E and occurs on viral and cellular mRNAs containing internal ribosomal entry sites (IRESs). Here we demonstrate that eIF4E availability plays a critical role in the switch from cap-dependent to IRES-mediated translation in picornavirus-infected cells. When both capped and IRES-containing mRNAs are present (as in intact cells or in vitro translation extracts), a decrease in the amount of eIF4E associated with the eIF4F complex elicits a striking increase in IRES-mediated viral mRNA translation. This effect is not observed in translation extracts depleted of capped mRNAs, indicating that capped mRNAs compete with IRES-containing mRNAs for translation. These data explain numerous reported observations where viral mRNAs are preferentially translated during infection.